Potential of Aedes aegypti populations in Madeira Island to transmit dengue and chikungunya viruses - Rocha Seixas, Gonçalo Filipe (2021)
BACKGROUND: Aedes spp. mosquitoes mainly transmit the arboviruses dengue virus (DENV) and chikungunya virus (CHIKV) in urban areas, causing a severe public health problem. In 2012-2013, a major dengue outbreak occurred on Madeira Island where the mosquito Aedes aegypti was the only vector. Up to now, the competence of Ae. aegypti populations from Madeira to transmit DENV or CHIKV remains unknown. This study aimed to assess experimentally the ability of Ae. aegypti populations from Madeira to transmit these viruses. RESULTS: By orally exposing mosquitoes to CHIKV (NC/2011-568) and DENV-2 (Bangkok), the vector competence of two field-collected Ae. aegypti populations, i.e. Funchal and Paúl do Mar, was evaluated. We found that both populations were similarly infected and ensured the dissemination and transmission of CHIKV at the same rates. With DENV-2, viral dissemination was significantly higher in the Funchal population compared to Paúl do Mar. We found no significant differences in transmission rates between populations. CONCLUSIONS: To our knowledge, this study has demonstrated for the first time the ability of temperate European Ae. aegypti populations from Madeira to transmit DENV and CHIKV. As our results suggest, there is a potential risk for the local transmission of DENV and CHIKV if introduced to Madeira or continental Europe where Aedes albopictus is present. Our results highlight the need for continuing vector surveillance and control on Madeira Island to future-proof the Island against mosquito-borne epidemics.